Enalapril decreases rat plasma concentration of TMAO, a gut bacteria-derived cardiovascular marker. (19th May 2018) - Konop, Marek; Radkowski, Marek; Grochowska, Marta; Perlejewski, Karol; Samborowska, Emilia; Ufnal, Marcin
Abstract: Introduction: Increased plasma level of trimethylamine N-oxide (TMAO), a bacterial metabolite of choline, is associated with an increased cardiovascular risk. Indoxyl sulfate, a bacterial metabolite of tryptophan, is thought to be associated with higher mortality in cardiorenal syndrome. We hypothesized that enalapril, a well-established drug reducing cardiovascular mortality, may affect the plasma level of gut bacteria-derived metabolites and gut bacteria composition. Materials and methods: 14–16-week-old Wistar rats were maintained either on water (controls) or water solution of enalapril for two weeks (5.3 or 12.6 mg/kg b.w.). Blood plasma and urine were analyzed for the concentration of TMAO and indoxyl sulfate using liquid chromatography coupled with triple-quadrupole mass spectrometry. Gut bacteria composition was analyzed with 16S rRNA gene sequence analysis. Results: Rats treated with enalapril showed a significantly lower plasma TMAO level and a trend towards higher 24 h urine excretion of TMA and TMAO. Plasma indoxyl level was similar between the groups. There was no significant difference between the groups in gut bacteria composition. Conclusions: Enalapril decreases rat plasma TMAO, but does not affect the plasma level of indoxyl sulfate and gut bacteria composition. The enalapril-induced decrease in plasma TMAO level may be of therapeutic and diagnostic importance.